Study protocol for the evaluation of an Infant Simulator based program delivered in schools: a pragmatic cluster randomised controlled trial - Brinkman, Sally; Johnson, S.; Lawrence, David; Codde, Jim; Hart, M.; Straton, J.; Silburn, Sven (BioMed Central, 2010)
Background: This paper presents the study protocol for a pragmatic randomised controlled trial to evaluate the impact of a school based program developed to prevent teenage pregnancy. The program includes students taking care of an Infant Simulator; despite growing popularity and an increasing global presence of such programs, there is no published evidence of their long-term impact. The aim of this trial is to evaluate the Virtual Infant Parenting (VIP) program by investigating pre-conceptual health and risk behaviours, teen pregnancy and the resultant birth outcomes, early child health and maternal health. Methods and Design: Fifty-seven schools (86% of 66 eligible secondary schools) in Perth, Australia were recruited to the clustered (by school) randomised trial, with even randomisation to the intervention and control arms. Between 2003 and 2006, the VIP program was administered to 1,267 participants in the intervention schools, while 1,567 participants in the non-intervention schools received standard curriculum. Participants were all female and aged between 13-15 years upon recruitment. Pre and post-intervention questionnaires measured short-term impact and participants are now being followed through their teenage years via data linkage to hospital medical records, abortion clinics and education records. Participants who have a live birth are interviewed by face-to-face interview. Kaplan-Meier survival analysis and proportional hazards regression will test for differences in pregnancy, birth and abortion rates during the teenage years between the study arms.Discussion: This protocol paper provides a detailed overview of the trial design as well as initial results in the form of participant flow. The authors describe the intervention and its delivery within the natural school setting and discuss the practical issues in the conduct of the trial, including recruitment. The trial is pragmatic and will directly inform those who provide Infant Simulator based programs in school settings.